Productive aging : concepts and challenges - Morrow-Howell, Nancy, 1952-; Hinterlong, James, 1970-; Sherraden, Michael W. (Michael Wayne), 1948- (Johns Hopkins University Press, 2001)
This book treats the implications of productive aging as challenges. It combines the theories of gerontology with practical considerations and acknowledging the contributions of leading researchers in the field of aging. As baby boomers are aging, they can hope to maintain a quality of life that previous generations have not enjoyed.